2014
DOI: 10.1080/00380768.2014.890015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of application of lime nitrogen and dicyandiamide on nitrous oxide emissions from green tea fields

Abstract: The aim of this study was to assess the mitigating effects of lime nitrogen (calcium cyanamide) and dicyandiamide (DCD) application on nitrous oxide (N 2 O) emissions from fields of green tea [Camellia sinensis (L.) Kuntze]. The study was conducted in experimental tea fields in which the fertilizer application rate was 544 kg nitrogen (N) ha −1 yr −1 for 2 years. The mean cumulative N 2 O flux from the soil between the canopies of tea plants for 2 years was 7.1 ± 0.9 kg N ha −1 yr −1 in control plots. The cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…, which means that they are much higher than those in other crop fields (Hirono and Nonaka 2014). Out of the inorganic NPK applied annually, only 25-50% are taken up by plants and the rest is lost through leaching, erosion, denitrification or volatilization (in the case of N), or is immobilized in soil organic matter (Roberts 2008).…”
Section: Environmental Consequences Of Intensive Use Of Fertilizers Imentioning
confidence: 99%
“…, which means that they are much higher than those in other crop fields (Hirono and Nonaka 2014). Out of the inorganic NPK applied annually, only 25-50% are taken up by plants and the rest is lost through leaching, erosion, denitrification or volatilization (in the case of N), or is immobilized in soil organic matter (Roberts 2008).…”
Section: Environmental Consequences Of Intensive Use Of Fertilizers Imentioning
confidence: 99%
“…A number of field studies for the continuous measurement of N 2 O fluxes from tea plantations in Japan (Akiyama et al ; Hirono and Nonaka, ; Hirono and Nonaka, ; Yamamoto et al ; Hou et al ), China (Fu et al ; Fu, ; Han et al ; Yao et al ) and India (Gogoi and Baruah, ), and data from East Asia have shown large amounts of N 2 O emissions from tea plantations, being much greater than those in cereal cropped fields on a hectare basis. Under common management practices, tea plantations can emit up to 61.0 kg N 2 O‐N ha –1 year –1 (Table ).…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…In Japan, lime‐N applications in tea plantations were shown to evidently reduce N 2 O emissions by 36–51% by inhibiting both nitrification and denitrification processes in acidic soils (Hirono and Nonaka, ; Yamamoto et al ), while in China, we carried out a two‐year investigation of continuously measuring N 2 O emissions from a conventional practice and six mitigation options in a commercial tea field in Hunan Province (Figure ). We found that mitigating N 2 O emissions from tea plantations is challenging, because only the treatments of white clover intercropping, deep fertiliser placement below 20 cm and controlled‐release fertiliser (CRF) at a half rate showed a limited reduction of N 2 O emissions, by 9.5%, 19.3% and 21.3%, respectively, compared with the conventional treatment.…”
Section: N2o Mitigation Optionsmentioning
confidence: 99%
“…The Ministry of Agriculture, Forestry and Fisheries of Japan authorized LN as a type of controlled-release fertilizer in 2013. Recently, the reduction of nitrous oxide emissions from the uplands and tea fields via the application of LN have frequently been verified, highlighting the nitrification inhibitory effect of this compound [6][7][8][9].…”
Section: Introductionmentioning
confidence: 98%